Criminal Behavior of Gangs in Aurora and Denver, Colorado, and Broward County, Florida: 1993-1994 - Huff, C. Ronald ([Verlag nicht ermittelbar], 2000)
This study was undertaken to measure the criminal behavior of gangs, including their involvement in delinquent behavior such as drug use and drug trafficking activities, and to compare gang behavior with that of youth who were at risk, but who had not yet become active in gangs. The project assessed the role that gangs play in the lives of youth whose living conditions are otherwise comparable. In order to study the criminal behavior of gangs, investigators sought to interview 50 gang members and 50 non-gang, at-risk youth at two sites in Colorado and one site in Florida. A large portion of the interview questions asked in both the gang member interview and the at-risk youth interview were parallel. The following variables appear in both the gang member and at-risk youth files (Parts 1 and 2 respectively) created for this data collection: gang popularity variables (respondents' perceptions of the positive and negative attributes of a gang, and why gangs endure over time), drug involvement variables (whether respondents or fellow members/friends sold various types of drugs, why selling drugs increases a person's "juice", the drug source organization, and where they traveled to get the drugs), criminal history variables (the reasons why respondents believed they were able to get away with crimes, their first arrest age, and their most serious arrest charge), personal activity variables (whether respondents or fellow members/friends participated in dances, sporting events, fighting, drug use or selling, shoplifting, assaulting people, or burglarizing homes), variables concerning the future (whether respondents would join a gang again/join a gang today, why some gangs survive and others don't, and how respondents see their future), and demographic variables (respondents' age, sex, race, city, neighborhood, school, school status, type of work, marital status, and relationship with parent(s)). In addition, Part 1, the Gang Member Data, contains gang status variables (gang symbols, gang nickname, gang turf, and how members define a gang) and gang membership variables (roles of the respondents within the gang, why members join a gang, what the most important gang rule is, and what happens to those who refuse the gang). Part 2, At-Risk Youth Data, contains additional variables on gang contact (the names of gangs who had approached the respondents, methods used to try to get the youths to join, how the youths refused the gang, and what happened as a result of refusing) and prevention (how at-risk youth would advise a young person to react if approached by a gang, and what the youths felt was the best way to prepare children to deal with gangs).